Factors related to CSF biomarkers examination in Alzheimer's disease: Biomarkers (non‐neuroimaging) / Method development and/or quality control. (7th December 2020) - Mao, Chenhui; Sha, Longze; Li, Jie; Huang, Xinying; Lei, Dan; Liu, Caiyan; Dong, Liling; Xu, Qi; Peng, Bin; Cui, Liying; Gao, Jing
Abstract: Background: Cerebral spinal fluid (CSF) biomarkers was important part of AT(N) framework in Alzheimer's disease (AD) definition. Typical AD biomarkers profile was decrease of Aβ42 and elevation of t‐tau and p‐tau in CSF. However, ELISA based CSF biomarkers examination was affected by many factors, including the sampling, transportation, storage of CSF, the environment and operation process. Also, the interpretation of results was influenced by many factors. Method: AD was diagnosed based on 2011NIA‐AA guideline and other dementia was diagnosed based on DSM‐IV. Other diseases without dementia were enrolled as control. Lumber puncture was performed after informed consent. Commercial accessible ELISA kits were introduced for measurement of CSF t‐tau, p‐tau, Aβ42 respectively by INNOTEST hTAU Ag, PHOSPHO‐TAU and β‐AMYLOID (1‐42) (Fujirebio, Ghent, Belgium). CSF was sub‐packed and stored at −80℃, which was tested half a year later. Also, we used two kinds of tubes to collect CSF in the same patient, one with low protein absorption and the other one not. Result: 58 AD, 83 other neurodegeneration and 28 controls were included. The difference between fresh and storage for half a year was calculated. The change of Aβ42 level in the three groups was 6.2, 13.9, −2.4pg/ml, t‐tau level was −184.6, −84.8, 301.8 pg/ml, p‐tau level was 15.3, 3.8, 2.5 pg/ml. Statistically significance was found in t‐tau and p‐tau difference. 4 AD and 7 non‐AD patients were enrolled in the study comparing two kinds of tubes. The change of Aβ42 level in the two groups was 49.7, 120.5pg/ml, t‐tau level was 186.3, 23.9 pg/ml, p‐tau level was 5.6, −4.8 pg/ml. Changes of tau level were more obvious, although not statistically significance. However, t‐tau/ Aβ42 ratio kept stable between the two kinds of tubes. Conclusion: CSF biomarkers examination was affected by collecting and storage. Tau level was significantly affected by storage, which would interfere with AD diagnosis, however, Aβ42 level was not. Low protein absorption tubes were strongly suggested when collecting CSF. Aβ42, t‐tau and p‐tau levels were all affected by absorption, while ratios were relatively stable. Ratios could reduce error of measurement to some extent. A strict standard of operation and laboratory quality control is determining factor in CSF biomarkers research.